The digital storytelling process: a comparative analysis from various experts - Hussain, Hashiroh; Shiratuddin, Norshuhada (2016)
Digital Storytelling (DST) is a method of delivering information to the audience.It combines narrative and digital media content infused with the multimedia elements.In order for the educators (i.e the designers) to create a compelling digital story, there are sets of processes introduced by experts. Nevertheless, the experts suggest varieties of processes to guide them; of which some are redundant. The main aim of this study is to propose a single guide process for the creation of DST.A comparative analysis is employed where ten DST models from various experts are analysed. The process can also be implemented in other multimedia materials that used the concept of DST.